STUDI PENERAPAN KONTROL PI UNTUK SISTEM KONTROL VALVE PADA LP DRUM PLTGU - Fitrianti, Friska Ayu; Anies Munawwaroh, Dita; Diah Larasati, Pengestuningtyas; Anggraeni Sugiono, Ratih (Journal of Mechanical Engineering and Applied Technology, 2025)
LP Drum (Low Pressure Drum) is a vapor reservoir from LP Evaporator (Low Pressure Evaporator) and LP Economizer (Low Pressure Economizer). The output of the LP Drum is in the form of saturated steam (steam content that has been separated from water) will be flowed into the steam turbine. There are several parameters that must be controlled, namely level, flow, pressure, and temperature on the LP Drum which affect valve performance. The parameters themselves are obtained from manufacturing, in this case MITSUBISHI as the main project. One of the valve control systems that can be used is Proportional Integral (PI). From calculations using MATLAB, the control system using the PI method obtained Kp = 0.218 and Ki = 0.028 seconds. The inaccuracy of LCV (Level Control Valve) is caused by the delay in receiving signals from DDC to LCV. These inaccuracies affect the values of LP feed water and LP steam flow change randomly and there is no definite reference value.